The Effect Of Coordination, Work Enthusiasm, Work Quality, And Work Capability On The Job Satisfaction Of Employees Of The Lahat Regency Education And Culture Office - Betti Anggreeni; Harun Samsuddin; Nisma Aprini (Utami Publisher, 2026)
This study aims to determine and analyze the influence of coordination, work enthusiasm, work quality and work ability individually and collectively on job satisfaction of employees of the Lahat Regency Education and Culture Office. The research method used in this study is a quantitative method using a questionnaire distributed to respondents. Data quality testing using validity tests, reliability tests and normality tests. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial tests, simultaneous tests and coefficients of determination. The results of the analysis obtained a regression equation, namely: Y = 0.903 + 0.541 (X1) + 0.292 (X2) + 0.351 (X3) + 0.409 (X4). The constant value is 0.903, this means that if the variables Coordination (X1), Work Spirit (X2), Work Quality (X3) and Work Ability (X4) are assumed to be zero or considered non-existent, then the value of the Job Satisfaction variable (Y) is 0.903. The magnitude of the influence of the Coordination variable (X1) on the Job Satisfaction variable (Y) is 0.541 or 54.1%. The magnitude of the influence of the Work Spirit variable (X2) on the Job Satisfaction variable (Y) is 0.292 or 29.2%. The magnitude of the influence of the Work Quality variable (X3) on the Job Satisfaction variable (Y) is 0.351 or 35.1%. The magnitude of the influence of the Work Ability variable (X4) on the Job Satisfaction variable (Y) is 0.409 or 40.9%. Research conclusion: Coordination, work enthusiasm, work quality and work ability have a significant influence, individually and collectively, on the job satisfaction of employees of the Lahat Regency Education and Culture Office.